Perspective Spiritual Intelligence QS. Luqman [31]: 12-19, Interpretation and Action - Aan Najib (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Allah gives intelligence to every human being to understand all the ways of thinking and acting properly and correctly in developing his mindset so that he is able to develop and think clearly to weigh, decide and face things by focusing on the problems faced with brilliant solutions. Spiritual intelligence is still a little empirical research conducted on this type of intelligence. This research is a literature research with descriptive analysis method. This study found that there is a link between spiritual intelligence and a better social life. The form of spiritual intelligence in QS. Luqman [31]: 12-19 are as follows: Prohibition of shirk, belief in Allah's retribution, commandments of prayer, amar ma'ruf and nahi munkar, commands to be patient, prohibitions being arrogant and lowering one's voice.